Buddhism: The Religion for the Equality of Gender - Khejoi, Sitthiporn; Weiangkae, Woratep; Thasa, Worrachat; Raisa-ngeuan, Saccarak; Jankhoon, Chatchawan (Journal of International Buddhist Studies, 2020)
It is universally accepted that like all human beings, women too, have a right to freedom from want, freedom from fear and freedom to live in dignity as their male counterparts do, all over the world. Yet, the position of women has always been a subordinate one. Despite protests, movements, agitations and other means of resistance, there has been no respite from this social evil. Gender discrimination continues even in the present times. There has been a steady decline in the proportion of the female sex all over the world as well as in India. Though the number of working women is increasing, there are certain fields in which the entry of women is still barred. In the world of sports, the female players are paid less than their male counter-parts. In the higher jobs too female diplomats, female politicians, female judges and female executives have a long way to go to attain the equality in proportion. The span of longevity, the rate of mortality and the range of immunization among the females are still the negative indicators. The slogans of equality are constantly raised but in actual practice, the situation has remained as grim as ever.